2019
DOI: 10.1002/ccr3.2264
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohyperphosphatemia in a patient with relapsed multiple myeloma after bone marrow transplantation: A case report

Abstract: Pseudohyperphosphatemia is a laboratory artifact characterized by falsely elevated serum phosphate mostly due to paraprotein interference on the conventional automated analyzer. Clinician recognition of this phenomenon and pre‐analytical preparation, including dilution or protein precipitation, can obviate unnecessary therapy and potentially unveil the diagnosis of paraproteinemia especially related to multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…They suggested the preparation of a blood sample with a protein-free filtrate prepared with trichloroacetic acid. 4 Pseudo-hyperphosphatemia has been reported in the past in patients with multiple myeloma 5,6 and it has been mostly associated with a laboratory artifact. The most commonly used technique to measure serum phosphate is by phosphomolybdate ultraviolet (UV) assay, which relies on UV absorption of ammonium phosphomolybdate complexes in the presence of sulfuric acid.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested the preparation of a blood sample with a protein-free filtrate prepared with trichloroacetic acid. 4 Pseudo-hyperphosphatemia has been reported in the past in patients with multiple myeloma 5,6 and it has been mostly associated with a laboratory artifact. The most commonly used technique to measure serum phosphate is by phosphomolybdate ultraviolet (UV) assay, which relies on UV absorption of ammonium phosphomolybdate complexes in the presence of sulfuric acid.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature identified total bilirubin, 24 HDL cholesterol 3,4 and phosphate 5 as additional Roche assays known to be affected by interference from paraproteins. Other assays reported to be affected by interference include albumin (bromcresol green), 8 urate (uricase), 6 calcium (arsenazo-III), 7 iron (ferrozine) 9 and total protein (biuret).…”
mentioning
confidence: 99%